Severe cutaneous drug reactions in Guinean children: a monocentric retrospective study of 35 cases - Thierno Mamadou Tounkara; Houleymatou Baldé; Mohamed Maciré Soumah; M'mah Bangoura; Boh Fanta Diané; Moussa Keita; Mamadou Djouldé Kanté; Fodé Amara Traoré; Fodé Bangaly Sako; Mariam Touré; Alhussein Doumbouya; Mohamed Cisse (Our Dermatology Online, 2018)
Background: Data on Severe cutaneous drug reactions (CADRs) are not common among in sub-Saharan Africa children. The purpose of this study was to document the clinical, etiological and evolutionary aspects of Severe CDRs in children hospitalized at the dermatology department of university hospitals of Conakry. Material and Methods: Retrospective study, conducted from 1 January 2000 to 31 December 2014. Were included all children aged 0-17 years hospitalized for severe CARDs. The data collected were Socio-demographic, clinical, para-clinical and evolution variables. The data was entered and analyzed using the Excel 8.0 software. Results: During a study period, 4437 patients of all ages was hospitalized in dermatology department. 35 patients were included with an average age of 11.3 years and a sex ratio of 1.5. The main clinical patterns were: Stevens Johnson syndrome 37.14% (13/35) Lyell syndrome 25.71 % and generalized bullous fixed eruption 22.85%. The drug was identified as 32 patients (91.42%): Sulfadoxine-Pyriméthamine 40.62%, cotrimoxazole 21.85%, nevirapin 12.5%, ampicillin 6.25%, traditional Pharmacopoeia 6.25% and griseofulin 3.12%. It was taken following self-medication in 14 patients, including a parental initiative in 9 patients. 7 patients had a history of drug allergy and 4 were HIV positive. We recorded 5 deaths. Conclusion: Our study confirms the rarity of severe CADRs in children. The importance of the sulfadoxine-pyrimethamine in the occurrence of severe CADRs in children is the particularity of our series.